LITERATURE REVIEW : THE INFLUENCE OF BRAND AMBASSADOR, BRAND LOYALTY, BRAND AWARENESS ON CUSTOMER SATISFACTION OF "K-EAUTY" COLLAGEN DRINK PRODUCTS IN BEKASI CITY - Dina Fitria Annuri (IJESM Indonesian Journal of Economics and Strategic Management, 2023)
This research is a literature review thatdiscussesoniaffect the brand ambassadorir, itiit mademeireik, brand awareiit isiss theifacetoisatisfactionisubscribe. This research uses aquantitative approach with a unit of analysis forcollagen drink “ K- eauty users.This research uses the SPSS statistical tool by testingvalidity and reliability for data suitability and classicalassumptions. Hypothesis testing is used to answertemporary guesses from answers by testing the t testand f test as well as determination.